No strings attached [wireless USB]. - Jones, W.D.
Electronics manufacturers are set to introduce products that cut the cords tethering USB (universal serial bus) peripherals to their hosts. Expected to provide unparalleled convenience to users, wireless USB allows effortless networking of electronic devices. Initially, wireless USB hookups will happen via a dongle connected to the host's USB port, and then eventually via embedded interfaces. Unfortunately, the issue concerning compatibility of wireless USB, which transfer data over the ultrawideband (UWB), has yet to be resolved mainly due to the current dispute between Freescale Semiconductor Inc., and Intel Corp., which are both vying for the right to call their versions of UWB the worldwide standard.
Keywords: Freescale Semiconductor Inc; Intel Corp; USB peripherals; UWB; Electronic device networking; Electronics manufacturers; Ultrawideband connection; Universal serial bus; Wireless USB